The self-concept of women with HIV and AIDS in Makassar - Utami, Ekawaty Hengki; Syarifuddin, Nurdiyanah; Rusmin, Muhammad (Al-Sihah: The Public Health Science Journal, 2020)
Women infected with HIV and AIDS are mostly victims of their husbands’ deviant behaviour. In that case, women with HIV and AIDS often suffer from psychological consequences that directly impact on their self-conception about their identities. This study employs phenomenological research method and selects its eight informants by snowball sampling technique. The informants consist of 6 women with HIV and AIDS, 1 counselling doctor, and 1 associate. The data were analysed with content analysis. The research findings suggest that most informants believe that they only gain knowledge about HIV and AIDS after they learn that they are infected by it through intervention programs. Prior to the intervention programs, they were not aware of the risks that the virus entails. The findings also report that the informants experience emotional turbulence after learning their condition even though it does not last long due to their realisation to their significant roles in the family as a mother and a wife. In addition to that, all informants sincerely hope for their recuperation, wish that their children do not carry the same virus in their bodies, and want to conceal the truth about their condition from the society. They are concerned of being rejected and discriminated by the society upon learning about the HIV and AIDS that they carry. All in all, psychological approach and counselling are significantly necessitated to help these women to maintain their positive self-conception.